Pengaruh Motivasi Terhadap Etos Kerja Karyawan Pada Skill Marketing Di Bank Muamalat KCP Stabat - Muhammad Da’i Arham; Nursantri Yanti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This research was conducted at Bank Muamalat KCP Stabat. The results of this study indicate the important factors of a leader to lead his company so that it is even better and must also be accompanied by strong motivation so that all employees have good performance and have presentation skills, the ability to ask questions, adaptability, and technical knowledge have a positive and significant influence on the skills of selling goods from the company.